The Effect of Being Aerobically Active vs. Inactive on Cutaneous Vascular Conductance during Local Heat Stress in an Older Population - Mitchell, Ulrike H.; Burton, Samantha; Gordon, Christopher; Mack, Gary W. (Frontiers in Physiology, 2017)
Objective: To test the hypothesis that long- term aerobically-trained elderly individuals have a greater amount of bioavailable nitric oxide (NO) and have a larger NO-mediated cutaneous vasodilation during local heat stress compared to their inactive elderly counterparts. Methods: Eight aerobically trained and 8 inactive older men (>60 yr old) participated in this study. NO bioavailability in blood and intradermal dialysate were measured with an ozone based chemiluminescence NO analyzer. Cutaneous vasodilator response to local heating was obtained using laser Doppler velocimetry. Results: Whole blood NO were similar in older- trained and inactive subjects (0.75 ± 0.56 and 0.38 ± 0.32 µM, respectively; Mann-Whitney, p = 0.153), as was intradermal dialysate NO before (7.82 ± 6.32 and 4.18 ± 1.89 µM respectively) and after local heating (7.16 ± 6.27 and 5.88 ± 3.97 µM respectively, p = 0.354. The cutaneous vasodilator response of the older- inactive group was smaller than the older- trained group (Group-Time interaction, F(24,264) = 12.0, p < 0.0001). When compared to a young group (previously reported data), the peak vasodilator response of the older- trained subjects was similar. However, the time to initial dilation was 3.1 and 2.2 times longer (p<0.05) in older- inactive and older- trained subjects, respectively, compared to young subjects. Conclusions: Our data support the hypothesis that the age-related reductions in NO-mediated cutaneous vasodilation can possibly be restored by maintaining an aerobic training regimen (at least 3 years). However, some residual effects of aging remain, specifically a delayed cutaneous vasodilator response to local heating is still present in active older adults. We found no evidence for an increase in systemic or local NO-bioavailability with an extended commitment to aerobic fitness.